ANALISIS PERBANDINGAN PENERAPAN METHOD NET BASIC DAN GROSS UP TERHADAP BEBAN PAJAK PENGHASILAN BADAN (Studi Kasus Pada PT.HI) - Imar Halimah (Universitas Pamulang, 2019)
The purpose of this study was to analyze the comparison of the application of the Net Method method and the Gross-up Method in the calculation of Article 21 Income Tax and find out which method was the most efficient used to save how much the Corporate Income Tax Expense (PPh owed by the agency) PT. HI, in this case the data analyzed is in 2011, 2012 and 2013.Data collection methods used in this study are secondary data obtained through documentation and observation of data for three years, namely in 2011 to 2013.The analytical method used in this study is descriptive analysis with a qualitative approach, namely research using documents or slowness, with data sources obtained from primary and secondary data, primary data is data obtained directly from the company, namely a general description of the company, data calculation of Income Tax Article 21 companies and profit and loss financial report data in 2011, 2012 and 2013. While secondary data is data processed by companies that are used as material for researchers. The results of this study indicate that there are differences between the net basic method and gross up method in the calculation of Article 21 Income Tax where the higher income tax payable if using gross up method with the acquisition of the difference in 2011 amounting to Rp.15,236,870, -, in 2012 of Rp. .19,573,460, - and in 2013 amounting to Rp.21,116,470, - but in this case the most efficient method of calculating Income Tax Article 21 on the calculation of income tax is owed by the corporate body using the gross-up method because by using gross up PPh method Article 21 payable can be financed in fiscal financial statements (uncorrected), while the net basic method of Article 21 Income Tax payable is made a positive correction so that the corporate corporate income tax burden is greater than using gross up method, and the results of comparison of calculations performed, gross method up does produce efficiency against Corporate Income Tax where companies can save money n income tax in 2011 amounted to Rp. 25,993,196, - in 2012 Rp. 34,605,170, - and in 2013 as much as Rp. 37,654,003.